1991
DOI: 10.1104/pp.97.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Plant NAD(H)-Glutamate Dehydrogenase Consists of Two Subunit Polypeptides and Their Participation in the Seven Isoenzymes Occurs in an Ordered Ratio

Abstract: The structure and function of NAD(H)-glutamate dehydrogenase in plants was studied by using grapevine (Vitis vinifera L. cv Sultanina) callus grown under different nitrogen sources. The enzyme consists of two subunit-polypeptides, a and ,B, with similar antigenic properties but with different molecular mass and charge. The two polypeptides have molecular masses of 43.0 and 42.5 kilodaltons, respectively. The holoenzyme is hexameric and is resolved into seven isoenzymes by native gel electrophoresis. Two-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
50
0
19

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 27 publications
8
50
0
19
Order By: Relevance
“…Transfer of electrophoretically resolved proteins onto nitrocellulose filters (0.2-mm pore size; Schleicher and Schuell) was performed according to Loulakakis and Roubelakis-Angelakis (1990b). GDH isoenzymes were localized in nondenaturating polyacrylamide gels using the in situ staining technique as analytically described by Loulakakis and Roubelakis-Angelakis (1991).…”
Section: Protein Extraction Enzyme Assays and Electrophoresismentioning
confidence: 99%
“…Transfer of electrophoretically resolved proteins onto nitrocellulose filters (0.2-mm pore size; Schleicher and Schuell) was performed according to Loulakakis and Roubelakis-Angelakis (1990b). GDH isoenzymes were localized in nondenaturating polyacrylamide gels using the in situ staining technique as analytically described by Loulakakis and Roubelakis-Angelakis (1991).…”
Section: Protein Extraction Enzyme Assays and Electrophoresismentioning
confidence: 99%
“…The seven NAD(H)-GDH isoenzymes in Arabidopsis are composed of two subunits that combine in different ratios in a manner similar to those of grape (Loulakakis and Roubelakis-Angelakis, 1991) and avocado (Loulakakis et al, 1994) NAD(H)-GDH isoenzymes; however, the subunit makeup of the anodal and cathodal isoenzymes in Arabidopsis are the reverse of those of grape and avocado. In Arabidopsis the slowest-migrating isoenzyme in a native gel, GDH1, is a homohexamer composed of a subunits, and the fastest-migrating isoenzyme, GDH7, is a homohexamer composed of /3 subunits.…”
Section: Dlscusslonmentioning
confidence: 99%
“…Data from feeding studies using grape calli also suggest that NAD(H)-GDH may play a role in nitrogen metabolism. Native PAGE analyses of protein extracts from grape calli treated with ammonia or Gln contained NAD(H)-GDH isoenzymes of high electrophoretic mobility (Loulakakis and Roubelakis-Angelakis, 1991). Two-dimensional gel electrophoresis of these samples revealed that they were composed of a single type of subunit designated a.…”
mentioning
confidence: 99%
“…In higher plants, GDH functions as a homohexamer or heterohexamer consisting of two subunits, a and b, that differ minimally in terms of their mass and charge. The a and b polypeptides combine in different ratios to form seven possible NADH-GDH isoenzymes in A. thaliana, N. plumbaginifolia or V. vinifera (Fontaine et al 2006;Loulakakis and Roubelakis-Angelakis 1991;Masclaux-Daubresse et al 2002). Only one isoform was found to be present in triticale, whereas L. luteus contains fourteen isoforms of this enzyme (Kwinta et al 2001;Ratajczak et al 1986).…”
Section: Introductionmentioning
confidence: 99%